Geometry design in rerfractive capillary optical fibers - Romaniuk, Ryszard S. (Photonics Letters of Poland, 2010)
The work presents a design method of capillary optical fiber (COF) geometry. A change of proportions in the capillary optical fiber drawn from a single preform or a set of crucibles is allowed on-line via the control of overpressure and thermal conditions in the outflow meniscus, which essentially lowers the manufacturing costs. Navier-Stokes and Hagen-Poissuille equations, adapted to the COF pulling geometry, were solved. The velocity fields give solutions to other quantities of interest such as mass flow rate, pulling force and COF geometry, including controlled capillary expansion and collapse. The results for COFs are for the following dimensions: internal diameters 1-100um, external diameters 30-300um, dimensional stability 1%. The major issue of the work is lowering capillary fiber fabrication costs. Full Text: PDF References: Y.T. Shah, et al.,"On the Stability of Nonisothermal Fiber Spinning-General Case", Ind. Eng. Chem. Fund. 11, 150 (1972).[CrossRef] B.P. Huynh, et al.,"Study of the non-isothermal glass fibre drawing process", Rheology Acta 22, 482 (1983).[CrossRef] A.N. Beris, et al.,"Time-dependent fiber spinning equations. 1. Analysis of the mathematical behavior", J. Non-Newtonian Fluid Mechanics 26, 341 (1988).[CrossRef] M. Myers,"A model for unsteady analysis of preform drawing", AIChE Journ. 35(4) 592 (1989).[CrossRef] H. Papamichael, et al.,"Thermal behavior of optical fibers during the cooling stage of the drawing process", J. Mater. Res. 6, 159 (1991).[CrossRef] J.N. Dewynne, et al.,"Slender viscous fibres with inertia and gravity", Q. J. Mech. Appl. Math. 47, 541 (1994).[CrossRef] A.D.Fitt, et al.,"Modeling the fabrication of hollow fibers: capillary drawing", JLT 19 (12), 1924 (2001).[CrossRef] A.D.Fitt, et al.,"The mathematical modelling of capillary drawing for holey fibre manufacture", Journ. of Engineering Mathematics 43(2) 201 (2002).[CrossRef] R.Romaniuk, et al., ETQ PAS, 52(3), 451 (2006)